The Concept of Land Ownership: Islamic Perspective - S. Salasal, Siti Mariam Malinumbay (Fakulti Kejuruteraan & Sains Geoinformasi, Universiti Teknologi Malaysia., 1998)
"It is He who has made the earth manageable for you, so traverse through its tracts and enjoy of the sustenance which He furnishes but unto Him is the resurrection." Surah AI-Mulk (67): 15